Halal Education and Promotion - Maliya, Laina; Malahayatie; Muslina (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2024)
The purpose of this article is to explain the role of education and promotion of halal business in Indonesia. This research uses qualitative research methods with a literature study approach based on several related articles and other scientific journals. The results of the discussion show that the role of education involving the community and awareness of sustainable behavior increases rapidly when offline and online initiatives are combined. Other education is a systematic process that aims to provide their full potential in intellectual and emotional aspects in improving about halal products, especially in countries with a majority Muslim population. with halal business education, society must integrate knowledge about halal products into the formal education curriculum by providing special training for professionals in the food, cosmetics, pharmaceutical and other services industries related to halal products. Meanwhile, halal business promotion includes various initiative programs aimed at increasing awareness, understanding and use of halal products and services. Namely, it is implemented by the government, non-government organizations and private companies to encourage consumption of halal products and support the halal industry.